Urban Poor Menghadapi Marjinalisasi Ruang dalam Akses terhadap Hak atas Kota di Pemukiman Rel Manggarai - Vallerian Antaresa; Ahmad Zaidan; Bima Wicaksana; David Jonathan; Aniqotul Ummah; Chomariyana Kartika Hesti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Infrastructure development and the transformation of urban space in Jakarta have driven changes in the function of strategic areas, including the Manggarai railway settlement, resulting in the increasing marginalization of the urban poor. The increase in the area's economic value has not been accompanied by inclusive spatial policies, resulting in low-income communities facing limited access to adequate housing and the right to the city. This study aims to analyze how spatial planning policies and infrastructure development operate as mechanisms for the production of spatial marginalization and limit the urban poor's access to the right to the city in the Manggarai railway settlement. The study used a qualitative approach using interviews with urban poor communities in the Manggarai railway settlement, supported by secondary data from journals, books, and policy documents. The results indicate that spatial marginalization occurs through the increase in the area's economic value, the lack of legal housing, and the weak integration of policies to protect vulnerable communities. These conditions result in limited access to basic services, increased vulnerability to eviction, and minimal citizen participation in decision-making regarding urban space. Spatial marginalization not only results in spatial exclusion but also systematically reinforces economic and political exclusion.